Causes and Consequences of Not Having a Personal Healthcare Provider Among American Indian Elders: A Mixed-Method Study - Elise Trott Jaramillo; David H. Sommerfeld; Emily A. Haozous; Amy Brunner; Cathleen E. Willging (Frontiers Media S.A., 2022)
Having a regular relationship with a healthcare provider contributes to better health outcomes and greater satisfaction with care for older adults. Although members of federally recognized American Indian tribes have a legal right to healthcare, American Indian Elders experience inequities in healthcare access that may compromise their ability to establish a relationship with a healthcare provider. This multi-year, community-driven, mixed-method study examines the potential causes and consequences of not having a personal healthcare provider among American Indian Elders. Quantitative surveys and qualitative interviews were conducted with 96 American Indian Elders (age 55 and over) in two states in the Southwestern United States. Quantitative and qualitative data were analyzed separately and then triangulated to identify convergences and divergences in data. Findings confirmed that having a consistent healthcare provider correlated significantly with self-rated measures of health, confidence in getting needed care, access to overall healthcare, and satisfaction with care. Lack of a regular healthcare provider was related to interconnected experiences of self-reliance, bureaucratic and contextual barriers to care, and sentiments of fear and mistrust based in previous interactions with medical care. Increasing health equity for American Indian Elders will thus require tailored outreach and system change efforts to increase continuity of care and provider longevity within health systems and build Elders' trust and confidence in healthcare providers.